Propagation of Albizia procera Benth. Using Cutting and Air Layering Techniques - Swamy, S.L.; Puri, S.; Yadav, S.B. (Indian Journal of Agroforestry, 2020)
Juvenile and mature stem cuttings of Albizia procera were tested for their rooting ability under green house condition. Cuttings were treated with different concentrations (100, 250, 500, 750 and 1000 mg/I) of auxins (IBA and NAA) and alsowith distilled water to serve as control. Mature cuttings did not root (irrespective of auxin treatments), while rooting was observed in juvenile cuttings. Among different treatments, water treated cuttings gave highest rooting (66.6 %), root number (33), root length (13.42 cm) and root nodulation. The biomass of shoot and root was also maximum in controlled treatment. In vivo rooting by air layering technique also showed higher rooting (55.5 %), root number and root length in controlled treatment as compared to IBA and NAA treatments. The ineffectiveness of difficult to root Albizia procera by auxin treatments is discussed.